PENERAPAN STRATEGI BELAJAR AKTIF INDEX CARD MATCH DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX MTsN LUMPO KABUPATEN PESISIR SELATAN - Permana, Ayu Rusta; Haryono, Yulia; Yuliana Fitri, Dewi (Pendidikan Matematika, 2014)
ABSTRACT This research was designed for revealing whether the mathematics conceptual understanding of the students taught by using Index Card Match active learning strategy was better than that of students taught by using conventional learning. This was an experimental research which used random toward the subject design. The population of this research was the student in class IX of MTsN Lumpo registered in academic year 2013/2014. The instrument of the research was an essay posttest whose reliability was 0,9420. Based on the result of data analysis, it was found that the average score of the students in the experimental class was 73,29 and in the control class was 59,29. In addition, the result of t-test indicated that P-value 0,305 was smaller than α = 0,05. Hence , it was concluded that the mathematics conceptual understanding of the students taught by using Index Card Match active learning strategy was better than that of students by using conventional learning in class IX MTsN Lumpo on level of significance 95%.